Pengembangan Media Pembelajaran Matematika Berbasis Android dan Ispring pada Materi Barisan dan Deret - Rindiani Esterina Bana; Ch. Krisnandari Ekowati; Irna K. S. Blegur (Mandalika Mathematics and Educations Journal, 2023)
This research aims to develop a valid, practical, and effective android and ispring based mathematics learning media of sequence and series materials. Researchers use the Research and Development (R&D) method with ADDIE (analysis, design, development, improvement, and design) development models as the research method. The data in this study is obtained from interviews, questionnaires, and tests. The result shows that the developed learning media meets the feasibility criteria of learning media are valid, practical, and effective. The validity average of subject experts is 4.75, and 4.52 for media experts by the "valid" category. The practicality average for teachers of the small class is 4.83 and 4.72 for teachers of the big ones, then, for students, it's 4.89 for the small ones and 4.85 for the big ones by the "practical" category. The percentage of students who pass the passing grade is 70% in the small class by the “effective”actegory and 82% in the big class by the "very effective" category.